The Role of ESG Disclosure as a Moderator of the Influence of Transfer Pricing and Managerial Ownership on Tax Aggressiveness in Energy Sector Companies Listed on the IDX (2022–2024) - Ni Putu Indah Budi Lestari Putra; Desak Nyoman Sri Werastuti; I Made Pradana Adiputra (Dinasti Publisher, 2026)
This study aims to examine the effect of transfer pricing and managerial ownership on tax aggressiveness, as well as to investigate the moderating role of Environmental, Social, and Governance disclosure. The study employs a quantitative approach using multiple linear regression analysis and Moderated Regression Analysis (MRA). The data were collected from the annual reports of energy sector companies listed on the Indonesia Stock Exchange (IDX) over a three-year period. Using a purposive sampling technique, the final sample consisted of 72 firm-year observations from 89 companies. The results indicate that transfer pricing has a positive and significant effect on tax aggressiveness, whereas managerial ownership has no significant effect. Furthermore, ESG disclosure is not found to moderate the relationship between either transfer pricing or managerial ownership and tax aggressiveness. These findings suggest that transfer pricing is one of the determinants of tax aggressiveness in energy sector companies, while ESG disclosure tends to be symbolic in nature and has not yet functioned effectively as a moderating mechanism.